Adsorption and electronic properties of pentacene on thin dielectric decoupling layers - Koslowski, Sebastian; Rosenblatt, Daniel; Kabakchiev, Alexander; Kuhnke, Klaus; Kern, Klaus; Schlickum, Uta (Beilstein Journal of Nanotechnology, 2017)
With the increasing use of thin dielectric decoupling layers to study the electronic properties of organic molecules on metal surfaces, comparative studies are needed in order to generalize findings and formulate practical rules. In this paper we study the adsorption and electronic properties of pentacene deposited onto h-BN/Rh(111) and compare them with those of pentacene deposited onto KCl on various metal surfaces. When deposited onto KCl, the HOMO and LUMO energies of the pentacene molecules scale with the work functions of the combined KCl/metal surface. The magnitude of the variation between the respective KCl/metal systems indicates the degree of interaction of the frontier orbitals with the underlying metal. The results confirm that the so-called IDIS model developed by Willenbockel et al. applies not only to molecular layers on bare metal surfaces, but also to individual molecules on thin electronically decoupling layers. Depositing pentacene onto h-BN/Rh(111) results in significantly different adsorption characteristics, due to the topographic corrugation of the surface as well as the lateral electric fields it presents. These properties are reflected in the divergence from the aforementioned trend for the orbital energies of pentacene deposited onto h-BN/Rh(111), as well as in the different adsorption geometry. Thus, the highly desirable capacity of h-BN to trap molecules comes at the price of enhanced metal–molecule interaction, which decreases the HOMO–LUMO gap of the molecules. In spite of the enhanced interaction, the molecular orbitals are evident in scanning tunnelling spectroscopy (STS) and their shapes can be resolved by spectroscopic mapping.
Keywords: hexagonal boron nitride (h-BN); metal insulating organic interface; pentacene; potassium chloride (KCl); scanning tunnelling microscopy (STM); scanning tunnelling spectroscopy (STS)